Pengaruh Media Sosial Dalam Penghayatan Nilai Ketuhanan - Rahmi Siregar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Social media plays an important role in shaping the realization of noble values ​​in society. Accessibility of information and communication through social media platforms facilitates wider and faster dissemination of religious teachings and values. This research aims to analyze the influence of social media on the appreciation of divine values. This research method uses a library method. The data collection technique used is the collection of literature data related to the influence of social media on the appreciation of divine values. The data obtained can be used to find out and increase understanding of individuals and society regarding the influence of social media on the appreciation of divine values.